Current Developments of Smoking and Vaping, Is Vaping Safer? - Arya Marganda Simanjuntak; Anastasya Hutapea; Bryan Steffanus Tampubolon; Stephani Browlim; Yosep Pebriyanto Napitupulu; Indi Esha Siregar; Suyanto Suyanto (Jurnal Respirasi, 2023)
Vape fans claim that vaping is the solution to smoking cessation, but this is still debatable. Even if vape is still considered new, numerous studies show that vaping is associated with lung injury (EVALI). Despite this, the trend of vaping is still increasing. This study aimed to review the current understanding of conventional smoking and vaping and compare both. Is vaping safer than smoking? Smoking has health risks for lung cancer, chronic obstructive pulmonary disease (COPD), stroke, and others, while vaping has been linked with EVALI. Local perfusions were decreased in tobacco smokers after exposure. However, perfusion increased in vaping after exposure. Bronchoalveolar lavage (BAL) in vape users showed an increase of vitamin E acetate, possibly causing impairment in lung structure and functionality of surfactant. This is the potential mechanism of EVALI in vape users. Smoking uses the Brinkman Index to determine the severity of smoking, but there is no index for vaping because it depends not on how many sticks but on how many e-liquids were used. It seems that vape is "safer” than smoking, but smoking and vaping both have their own health risks, and it is safe to assume that neither is safe for use. "Vape is the solution for smoking cessation” needs further research because it takes years to understand conventional smoking in relation to other diseases. Prospective follow-up studies to determine the risk of vaping on other diseases are needed in the future.